Microglia contribute to bipolar depression through Serinc2-dependent phospholipid synthesis - Ying-Han Wang; Chong-Lei Fu; Lin-Bo Chen; Chu-Yi Zhang; Jian-Shan Chen; Qiao-Ming Zhang; Yirui Liang; Rui-Lan Yang; Yu Li; Ya-Ni Zhang; Yi-Nuo Han; Zhen-Liang Yuan; et al. (Proceedings of the National Academy of Sciences, 2025)
Although clinical research has revealed microglia-related inflammatory and immune responses in bipolar disorder (BD) patient brains, it remains unclear how microglia contribute to the pathogenesis of BD. Here, we demonstrated that Serinc2 is associated with susceptibility to BD and showed a reduced expression in BDII patient plasma, which correlated with the disease severity. Using induced pluripotent stem cell (iPSC) models of sporadic and familial BDII patients, we found that Serinc2 expression showed deficits in iPSC-derived microglia-like cells, resulting in decreased synaptic pruning. Further, combining the microglia-specific Serinc2-deficient mouse and iPSC-microglia models, we found that microglial Serinc2 deficits functioned through attenuating the synthesis of serine-related phospholipids in the plasma membrane, thus resulting in depression-like behavioral abnormalities in the animals. Finally, we showed that the Serinc2-dependent lipid deficits diminished microglial membrane CR3 formation to interrupted synaptic pruning signals from neurons. Therefore, our results indicated that Serinc2 deficits in microglia might contribute to the pathogenesis of BD.